Pengembangan Diversifikasi Produsen Whiskey melalui Digital Marketing di desa Marihat Jaya, Kota Pematangsiantar - Leo Fernando Simatupang; David Togi Hutahaean (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The purpose of the implementation of this Community Service is to provide knowledge to the community, especially MSME players who produce young whiskey about digital marketing at Whiskey Producers in Marihat Jaya village, Pematangsiantar City, Kayugiyang Village, Garung District, Wonosobo Regency, marketing training using internet media. The implementation of the training was carried out in several stages including surveying the location of activities and MSMEs in Kayugiyang village. Planning stage, this stage is the stage of preparing plans and identifying program planning that will be implemented, then formulating various needs in planning an online marketing system. Socialization, socialization activities provide initial knowledge about online marketing to the community or MSME producers of Whiskey in Marihat Jaya village, Pematangsiantar City and provide delivery of the draft program of activities to be carried out. Implementation, this stage carries out google business account registration activities for people who have a business. Evaluation, this activity is carried out after completing the activity program. The community was very enthusiastic, marked by the many participants who attended the digital marketing training for the improvement of Whiskey Producer MSMEs in Marihat Jaya village, Pematangsiantar City.